Disasters Impacting Negatively on Education: A Call for Renewed Intervention Strategies in Kenya - Ndiku, Judah M (Advances in Social Sciences Research Journal, 2015)
Natural and man-made disasters have wreaked havoc in society since time immemorial. Kenya has not been spared by the wide spread of such disasters. As demonstrated, disasters keep on reoccurring with higher intensity than before with an attitude and mode of operation of responding after the disasters have struck. This happens in a back drop of a more conscious society which is aware of its rights. Such a society may demand its rights for protection as a basic right enshrined in the Kenya Constitution 2010 and other international protocols. Out of this thinking, it may be necessary to rethink of novel ways to mitigate disasters especially among the most vulnerable, school going children. This paper discusses the different disasters and their impact in Kenya. Emphasis has been put on the impact of disasters on education. The paper suggests new ways to mitigate disasters affecting school children in line with the new thinking articulated in the literature in Education in Emergencies. A call for more conscious societies to take action to intervene on disasters affecting children is recommended.